Ethical Leadership from Islamic Perspectives: A Model for Social and Organisational Justice - Randeree, K (Common Ground, 2008)
The Arab world had a proud tradition of providing security to its working class especially during the early Islamic period. To be relevant in the future, however, developing Arab societies will need to re-examine their currently Euro-centric premise and strive to serve global equity through a more balanced philosophy, one that acknowledges their rich cultural heritage whilst simultaneously embracing the need for modernisation and advancement. Thus, the contemporary strategist in the Arab world needs to be inspired by the humanism of the early Islamic scholars, such as Abu Hamid Muhammad Al-Ghazzali (1058-1111). The principles for good governance (knowledge, justice, wisdom and tolerance) were articulated by Al-Ghazzali a millennium ago and remain valid today. Using Dubai as a model for change, this paper proposes a paradigm shift in work ethic inspired by early Muslim practitioners for creating sustainable and moderate Arab societies in the 21st century. It further demonstrates the ability of the growing regional knowledge economy to adapt economically and socially by implementing traditional ethical guidelines to achieve sustainable growth in addition to avoiding the exploitation of a largely foreign labour class.